2017
DOI: 10.15395/mkb.v49n2.1056
|View full text |Cite
|
Sign up to set email alerts
|

Cinico-Epidemiological Profile of Vitiligo Patients in Dr. Hasan Sadikin General Hospital Bandung

Abstract: Vitiligo is the most common hypopigmentation disorder; however, until now there iss no comprehensive epidemiological-clinical study of vitiligo in Indonesia. A descriptive study using a questionnaire among vitiligo patients in Dr. Hasan Sadikin General Hospital Bandung was conducted to determine the clinical findings, sociodemographic factors, coexisting autoimmune disorders, and severity of disease. All vitiligo patients were recruited during the period of February 2012 to April 2014 from the Dermatology Outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…This result was conducted by Dwiyana study, who reported that the majority occupations of vitiligo patients were students (30.99%) and housewife (21.49%). 11 The result of the occupation in this study were less useful because they were unable to investigate factors that may have triggered the onset of vitiligo in patients.…”
Section: Methodsmentioning
confidence: 91%
“…This result was conducted by Dwiyana study, who reported that the majority occupations of vitiligo patients were students (30.99%) and housewife (21.49%). 11 The result of the occupation in this study were less useful because they were unable to investigate factors that may have triggered the onset of vitiligo in patients.…”
Section: Methodsmentioning
confidence: 91%
“…This is because women are more likely than men to be the breadwinners in modern society, so they are either too busy or indifferent to the need for vitiligo treatment. 4 Additionally, female patients tend to have more cosmetic concerns and have more free time for longterm therapy. 5 Age group representation revealed that 26.92% of respondents were between the ages of 0-14 years, 26.92% were between the ages of 15-24 years, 38.5%…”
Section: Discussionmentioning
confidence: 99%
“…Fauzia et al (2020) andDwiyana et al (2017) state that, commonly, there were more patients with unstable vitiligo than stable vitiligo 4,5. Patients with vitiligo in our hospital may not seek treatment once the disease first manifests due to…”
mentioning
confidence: 89%
“…For example, Khurrum, AlGhamdi, Bedaiwi, & AlBalahi (2017) found that 28% of vitiligo patients had the Koebner phenomenon. Other studies have suggested that the presence of the Koebner phenomenon in active lesions does not always indicate the severity of vitiligo, however vitiligo can also occur due to genetic factors (Dwiyana et al, 2017;Wolff, Johnson, Saavedra, & Roh, 2017). In this study, two of the new vitiligo patients who received NB-UVB radiation therapy and four who received topical corticosteroid therapy had genetic triggers.…”
Section: Clinical Overview Of Vitiligo Patientsmentioning
confidence: 97%